2015
DOI: 10.7475/kjan.2015.27.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Disease Experience of Korean Women with Eating Disorders

Abstract: Purpose: This study was aimed to explore and describe the disease experience of Korean women with eating disorders within psychological and sociocultural context. Methods: The participants were 12 young adult women suffering with eating disorders or have recovered from the diseases. Data were collected via in-depth interviews and analyzed according to the grounded theory methodology by Strauss and Corbin. Results: The core category of the disease experience was 'becoming the master of life through desperate ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…This study identified shame and stigma as major causal conditions. This finding is consistent with previous studies on various Korean patients with chronic disease who are stigmatized by society, such as epilepsy patients [37], patients with an ostomy [38], women with eating disorders [39], and adults with hemophilia [40]. Thus, it is necessary to promote public awareness to minimize stigma and to support people with disabilities on a social level.…”
Section: Discussionsupporting
confidence: 90%
“…This study identified shame and stigma as major causal conditions. This finding is consistent with previous studies on various Korean patients with chronic disease who are stigmatized by society, such as epilepsy patients [37], patients with an ostomy [38], women with eating disorders [39], and adults with hemophilia [40]. Thus, it is necessary to promote public awareness to minimize stigma and to support people with disabilities on a social level.…”
Section: Discussionsupporting
confidence: 90%